1995
DOI: 10.1038/ki.1995.22
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and echocardiographic disease in patients starting end-stage renal disease therapy

Abstract: End-stage renal disease (ESRD) patients have a high cardiovascular mortality rate. Precise estimates of the prevalence, risk factors and prognosis of different manifestations of cardiac disease are unavailable. In this study a prospective cohort of 433 ESRD patients was followed from the start of ESRD therapy for a mean of 41 months. Baseline clinical assessment and echocardiography were performed on all patients. The major outcome measure was death while on dialysis therapy. Clinical manifestations of cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
746
4
20

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,154 publications
(809 citation statements)
references
References 32 publications
39
746
4
20
Order By: Relevance
“…Reduced LVEF has been associated with adverse cardiovascular events in ESRD patients 42. In agreement with previous studies,12, 43 we also demonstrated that a reduced LVEF was an independent predictor for both all‐cause and cardiovascular mortalities in hemodialysis patients 12…”
Section: Discussionsupporting
confidence: 91%
“…Reduced LVEF has been associated with adverse cardiovascular events in ESRD patients 42. In agreement with previous studies,12, 43 we also demonstrated that a reduced LVEF was an independent predictor for both all‐cause and cardiovascular mortalities in hemodialysis patients 12…”
Section: Discussionsupporting
confidence: 91%
“…In the Canadian Prospective Cohort Study of 433 incident dialysis patients, 74% had LVH at baseline, 44% had concentric LVH, 30% had hypertrophy with left ventricular dilatation, and 15% had systolic dysfunction. 18 …”
Section: Cvd In Kidney Failurementioning
confidence: 99%
“…From previous studies (24,25), a SD of 30 g/m 2 was assumed for the change in LVMi (26). A sample size of 75 patients per treatment arm was needed to detect a difference in LVMi of 15 g/m 2 at a two-sided significance level of 5%, with a power of 80% and an attrition rate of 20%.…”
Section: End Pointsmentioning
confidence: 99%